1992
DOI: 10.1007/bf02550117
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral ultrasonography, fiberoptic cystoscopy and bladder washout cytology in the evaluation of bladder tumours

Abstract: The impact of transurethral ultrasonography, fiberoptic cystoscopy and bladder washout cytology on assessment of bladder tumours was investigated in this study. Transurethral ultrasonography had an accuracy rate of 96.5% in diagnosing and staging bladder tumours. The accuracy rates of fiberoptic cystoscopy and washout cytology were 90.9% and 73.7%, respectively, in diagnosis. The efficacy of transurethral ultrasonography was found to be high enough for routine employment in the evaluation of the bladder tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Abdominal ultrasound is useful to assess tumor size, degree of bladder wall invasion, and abdominal metastasis. 259 Currently, CT urography and MRI are preferred for diagnosing and staging bladder tumors. In humans, the current opinion is that the extent of invasion of the bladder wall cannot be accurately assessed by transabdominal ultrasound.…”
Section: Foreign Bodiesmentioning
confidence: 99%
“…Abdominal ultrasound is useful to assess tumor size, degree of bladder wall invasion, and abdominal metastasis. 259 Currently, CT urography and MRI are preferred for diagnosing and staging bladder tumors. In humans, the current opinion is that the extent of invasion of the bladder wall cannot be accurately assessed by transabdominal ultrasound.…”
Section: Foreign Bodiesmentioning
confidence: 99%
“…Aside from TAUS, other approaches include transurethral US and endoluminal US, also known as intravesical US. Akdas et al [73] reported an overall accuracy of 97% in diagnosing and staging bladder tumors with transurethral US in 104 patients: 96% for stage Ta-T1 lesions, 100% for T2 lesions, 92% for T3 lesions, and 100% for T4 lesions. Endoluminal US uses a miniature, high-frequency transducer introduced by a rigid cystoscope for intravesical evaluation [74,75].…”
Section: Usmentioning
confidence: 99%